Gambaran Self Disclosure Remaja yang Mengalami Broken Home - Hilwa Dinda Salsabila; Elis Suci Prapita Sari Abdullah (JURNAL PSIMAWA, 2021)
Broken home will affect teenager development. Teenagers coming from a broken family will lose their way, find it difficult to trust others and even tend to do negative things. Teenagers need direction from their parents in their developments. Therefore, teenagers need to be able to express themselves, find solutions to problems they are facing and need guidance in order that they not feel alone in solving their problems. This study aims to determine the depiction of self-disclosure of teenagers from broken homes with phenomenological qualitative research methods. In collecting the data, researchers used semi-structured interview techniques and unstructured observations. The research subjects were two teenagers aged 15-18 years, male and female. The results of this study indicate that male teenager has less self-disclosure than female teenager, which is marked by the inability of the individual to express himself in detail or thoroughly. Meanwhile, female teenager is able to express herself in detail and thoroughly to others. Both subjects also prefer to disclose themselves intensely to their family rather than friends because they consider their family a trusted person.